A survey of dairy cattle management, crop planning, and forages cost of production in Northern Italy. Issue 1 (2nd January 2019) - Bellingeri, Andrea; Cabrera, Victor; Gallo, Antonio; Liang, Di; Masoero, Francesco
Abstract: A survey regarding crop enterprise management, forages cost of production, dairy cattle management including reproductive management, housing, heat abatement, body condition scoring, nutrition, grouping strategies, and income over feed cost performance, was carried out from December 2016 to January 2018 on 50 dairy farms by the Department of Animal Science, Food and Nutrition of Università Cattolica del Sacro Cuore (Piacenza, Italy). A total of 41 herds (82%) completed the survey. Average herd size was 327 ± 162 lactating cows with the average land size of 160 ± 94 ha per farm. Herds were located in the provinces of Cremona (17), Brescia (8), Mantova (7), Piacenza (5), Cuneo (4), Bergamo (3), Lodi (3), Torino (2), and Venezia (1). These farms sold 32.8 ± 2.01 kg of milk/day per cow, had an annual culling rate of 34.0 ± 4.00%, a calving interval of 14.16 ± 0.58 months., and a 21-days pregnancy rate of 17.05 ± 2.58%. Implementing effective management strategies to contrast the damage caused by Ostrinia nubilalis, Diabrotica spp . and Myocastor coypus were identified as the main crop enterprise challenges. Main forages cultivated were alfalfa and corn silage second seeding with a total cost of production of (€/ha) 1968 ± 362 and 2, 581 ± 221, with an average yield of 9.61 ± 1.24 and 17.22 ± 2.46 ton of DM per hectare, respectively. Results of this study can provide useful benchmark or reference for dairy management practices, crops and dairy performances, forages production costs on very well-managed North Italian dairy farms at the present time. Highlights: benchmarks for dairy farms management practices, economic and reproductive performance cost of production of forages in northern Italy